1998
DOI: 10.1080/17843286.1998.11754164
|View full text |Cite
|
Sign up to set email alerts
|

Dyskeratosis Congenita and Associated Interstitial Lung Disease: A Case Report

Abstract: We describe a male patient with dyskeratosis congenita who, in addition to the classic triad, also suffers from usual interstitial pneumonia. He was treated with methyl-prednisolone but it is not clear whether this had an influence on the course of the disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2001
2001
2009
2009

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…Whenever available, biopsy or post-mortem histopathological investigations of lung tissue have revealed the common occurrence of interstitial fibrosis. In the patient described here, as well as in two other cases,15 16 the interstitial fibrosis was found to be similar to that of UIP. Others have concluded that the risk of restrictive pulmonary disease of unknown aetiology is increased in patients with DC 13.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Whenever available, biopsy or post-mortem histopathological investigations of lung tissue have revealed the common occurrence of interstitial fibrosis. In the patient described here, as well as in two other cases,15 16 the interstitial fibrosis was found to be similar to that of UIP. Others have concluded that the risk of restrictive pulmonary disease of unknown aetiology is increased in patients with DC 13.…”
Section: Discussionsupporting
confidence: 80%
“…Since 1995 patients have been reported in the DC registry established at the Hammersmith Hospital. London6; one additional case was reported in 1998 and is not included in the registry 16. Both patients described here are included in the registry.…”
Section: Discussionmentioning
confidence: 99%
“…They occur in 20% of patients, mainly adults with pulmonary fibrosis and lung biopsy showing usual interstitial pneumonitis (UIP). [4][5][6][7][8] Interstitial lung fibrosis was also described in children with DKC after bone marrow transplantation. 9 However, pulmonary disease in DKC may be underestimated because most patients die at an early age from bone marrow failure.…”
Section: Discussionmentioning
confidence: 99%
“…1 Autopsy or surgical lung biopsy findings have been described in only 8 patients reported previously in the English language literature (Table 1). 5,[11][12][13][14][15][16] Usual interstitial pneumonia was described in surgical lung biopsy specimens from 3 of these patients, none of whom had undergone BMT. [11][12][13] With the addition of our 2 patients, UIP was present in 5 of 7 patients who underwent surgical lung biopsy.…”
Section: Discussionmentioning
confidence: 99%